1998
DOI: 10.1002/(sici)1097-4636(199810)42:1<20::aid-jbm4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of surface-blasted implants made of titanium alloy and cobalt-chromium alloy in a rabbit intramedullary model

Abstract: The purpose of this study was to compare the osseointegration of surface-blasted Ti6A14V and CoCr implants in vivo. Ti6A14V and CoCr rods blasted with 710 microm A12O3 particles were bilaterally press-fit into the medullary space of distal femora of 24 rabbits. Evaluation was made radiographically, histologically, histomorphometrically (3, 6, and 12 weeks after implantation), and mechanically (12 weeks). Both Ti6A14V and CoCr implants demonstrated good biocompatibility radiographically and histologically. Tolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 29 publications
3
66
0
2
Order By: Relevance
“…However, this ability can cause critical complications when they removed from human bone. When Ti alloys are used for bone xators such as bone screws and intramedullary nails, Ti alloys form new bone on them and sometimes assimilate with original bone (osseointegration) [6][7][8] . Therefore, bone may be re-fractured when the xators are retrieved after bone healing [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this ability can cause critical complications when they removed from human bone. When Ti alloys are used for bone xators such as bone screws and intramedullary nails, Ti alloys form new bone on them and sometimes assimilate with original bone (osseointegration) [6][7][8] . Therefore, bone may be re-fractured when the xators are retrieved after bone healing [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, surface treatments that do not cause bone formation are necessary for the safe utilization of Ti alloy. However, most of surface treatment techniques studied in the eld of biomaterials have targeted bone formation around Ti alloy [6][7][8][15][16][17] . Surface treatment techniques to inhibit bone formation around Ti alloy have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…15 Bone ingrowth into pores causes interlocking of the surrounding bone tissue with the implant, and may result in improved in vivo biomechanical stability and higher resistance to fatigue loading. 27 A study by Götz et al 28 showed that initial bone ingrowth is preferentially directed toward the pores of the implant. Thus, an added advantage is that laser-textured implants with open pores may provide improved stability during early stages of osseointegration.…”
mentioning
confidence: 99%
“…It is known that, when the surface of a titanium implant is roughened, bone apposition onto the implant surface and bone-implant interfacial strength is increased [10]. This property seems not peculiar to titanium alloy [11], and it is possible that the roughened surface of the stainless steel nail accelerated osteoconduction on the nail surface. Unlike the surface of the metal implants for cementless arthroplasties, the surface of the metals for osteosynthesis would not have to be highly osteoconductive.…”
Section: Aizawa Et Al J Med Cases 2015;6(3):105-108mentioning
confidence: 99%